STRATEGI PENGEMBANGAN OBJEK PARIWISATA PEMANDIAN ALAM BANYU BIRU KABUPATEN PASURUAN - Haniawati, Dian; Supriliyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
The Pasuruan Regency Office has a target to increase tourism productivity and cultural arts, but in its realization there are still problems, namely undirected tourism development, marketing strategies that are not optimal, lack of public awareness of the potential of the area owned, building functions that are not used properly, and low human resources. In this case using strategic planning analysis according to John M. Bryson and SWOT analysis techniques according to Freddy Rangkuti. This type of qualitative descriptive research. Sources of data are primary data and secondary data. The technique of determining the informant is snowball. The SWOT matrix produces an alternative strategy of Strength, Opportunities (SO) in the form of eight alternative strategies. There are five strategies to choose from as a priority scale Keywords: Tourism Objects, Strategic Planning Process, SWOT Analysis